Hosting capacity aspects in distribution networks towards sustainable energy systems - Mousa, Hossam H. H.; Mahmoud, Karar; Lehtonen, Matti (Elsevier, 2025)
Hosting Capacity Aspects in Distribution Networks Towards Sustainable Energy Systems is a comprehensive guidebook that delves into the critical aspects of power systems. It emphasizes the essential developments necessary to support the transition towards sustainable energy sources. The book begins by laying down the fundamental principles of hosting capacity in energy systems, highlighting modern challenges in the shift to renewable and distributed energy sources. It underscores the pivotal role hosting capacity plays in the planning and operation of successful systems, offering readers a solid foundation on which to build their understanding. Subsequent chapters are dedicated to providing detailed explanations on various practical hosting capacity calculation methods and enhancement techniques. The book also introduces available tools and software solutions to address hosting capacity issues. By compiling the latest insights and advancements in this crucial yet under-explored area, this book serves as an invaluable resource for students, researchers, and engineers. It aids in planning hosting capacity aspects for the successful integration of renewable and sustainable energy systems.